Canine Olfactory Detection of SARS-COV2-Infected Patients: A One Health Approach - Maia, Rita de Cássia Carvalho; Alves, Leucio Câmara; Silva, Jeine Emanuele Santos da; Czyba, François Rémi; Pereira, Jorge Antonio; Soistier, Vincent; Julien, Clothilde Lecoq; Grandjean, Dominique; Soares, Anísio Francisco (Frontiers in Public Health, 2021)
The aim of the present study is to apply the canine olfactory sensitivity to detect COVID19-positive axillary sweat samples as a One Health approach in Latin America. One hundred volunteers with COVID-like symptoms were invited to participate, and both axillary sweat samples for dog detection, and nasopharynx/oropharynx swabs for qPCR were collected. Two dogs, previously trained, detected 97.4% of the samples positive for COVID-19, including a false-negative qPCR-test, and the positive predictive value was of 100% and the negative predictive value was of 98.2%. Therefore, we can conclude that canine olfactory sensitivity can detect a person infected with COVID19 through axillary sweat successfully and could be used as an alternative to screen them without invasive testing.